Idea Improvement and Socially Shared Regulation Matter in Cross-Cultural Online Collaborative Learning. (January 2023) - Fosua Gyasi, Juliana; Zheng, Lanqin
Cross-cultural collaborative learning has been paid more and more attention in recent years. To promote productive cross-cultural collaborative learning, idea generation and improvement, and socially shared regulation is crucial. The study aimed to identify the differences in idea generation and improvement as well as socially shared regulation between high- and low-performance groups in cross-cultural online collaborative learning. In this study, 24 culturally diverse university students composed of eight groups conducted cross-cultural online collaborative learning to solve problems collaboratively. Epistemic network analysis and lag sequential analysis methods were employed to analyze data quantitatively and qualitatively. The results revealed that different strategies shape different learning performances. High-performance groups adopted more cognitive, social, and regulation processes than low-performance groups. The results extend the existing literature by indicating that idea elaboration, refining or building on ideas, and appraisal is strongly connected to new ideas. In addition, transitions from monitoring and controlling to adapting metacognition in collaborative learning activities are the main difference in socially shared regulation between high-performance and low-performance groups. This study shed light on how to engage culturally diverse students to generate and improve ideas as well as jointly regulate collaborative learning.